MENINGKATKAN KREATIVITAS MATEMATIKA SISWA DENGAN STRATEGI PEMBELAJARAN INKUIRI - Azizah Yusra Amaliyah Harahap; Adinda Pratiwi (JURNAL TEMATIK, 2020)
The problem in this study is the low mathematics creativity and student activity in mathematics learning in grade 2sd junior hight school Negeri 4 Panyabungan on the subject of Cubes and Blocks. The purpose of this study was to improve students' mathematical creativity on the subject of cubes and blocks and also to increase student learning activities by implementing inquiry learning strategies in the learning process. This type of research is classroom action research. The results of creativity obtained from research in the first cycle of 53.85% were complete and the second cycle was 80.77% of the 26 students who took the learning test. Based on the results of the study it can be concluded that there is an increase in students' mathematical creativity, student activity and the ability of teachers to apply inquiry learning strategies in class VIII-I of SMP Negeri 4 Panyabungan